MEDIA PEMBELAJARAN AUGMENTED REALITY KLASIFIKASI MAKHLUK HIDUP 5 KINGDOM DENGAN METODE MARKER BASED BERBASIS ANDROID - Romadhoni, Dadan; Tri Ferga Prasetyo (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2021)
In this era of globalization, the development of information technology and communication has become endemic among the general public. As it goes time, Augmented Reality is growing so rapidly that it is possible the development of this application in various fields including education. Use computers for educational purposes that are increasingly widespread, especially in developed countries, is a fact that shows that with this media indeed it is possible to carry out a more teaching and learning process effective. Augmented Reality is an amalgamation of two worlds, namely virtual world to the real world, in other words, objects in the virtual world can be us show it to the real world. This learning media is expected to be used effectively by junior high school students.